Mediating Assurance in Auditing Standards: Auditors Mitigation of Risks of Frauds - Imoniana, Joshua Onome; Bianchi, Massimo (Universitas Muhammadiyah Surakarta, 2024)
This study critically interrogates mediating assurance in auditing lived experiences of independent auditors. It is qualitative research based on constructivist perspective. A combination of participant observations and interviews were used to build data corpus. Data was analysed using thematic coding. Findings show that assurance is felt in the present auditing standards, corroborated by mediating assurance while drawing on the main objectives of auditing. Findings also show that ISA motivates the verification of accounting functions disrupting status quo for perpetuation of fraud outside the outreach of auditor. Therefore, the auditor tends to mold credibility with its works, towards reducing auditing expectation gap. As the auditor reports to the corporate governance, mainly the audit committee, certain cases may reveal barriers for additional audit jobs to elucidate cases of significant accounting errors that have the characteristics of accounting fraud. We conclude that, insofar as the ISA tries to favour a set of auditors who suppress compliance or auditor with a myopic approach, the main motivations of assurance would not have been met. As an implication, it constitutes an innovation in the fieldwork of the auditors to embrace the current responsibilities demanded by users of financial statements to mitigate the risk of fraud.